If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 = 3y + 3 Reorder the terms: -18 = 3 + 3y Solving -18 = 3 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -18 + -3y = 3 + 3y + -3y Combine like terms: 3y + -3y = 0 -18 + -3y = 3 + 0 -18 + -3y = 3 Add '18' to each side of the equation. -18 + 18 + -3y = 3 + 18 Combine like terms: -18 + 18 = 0 0 + -3y = 3 + 18 -3y = 3 + 18 Combine like terms: 3 + 18 = 21 -3y = 21 Divide each side by '-3'. y = -7 Simplifying y = -7
| (2-k)-3(4k+2)= | | 300=75+1.25x | | 3-10b=26+9 | | 6-3y=3x | | 2d-9=11 | | 3y-11y=56 | | 38a=5 | | 4000=100x | | 5x+100=15x+50 | | c=100+0.85(250) | | 14+b=a | | 6n+5=11 | | 750=100x | | 5(v-3)=-5v+45 | | 500-25w=200 | | 4x+6y=386 | | 9n-3=9n+24 | | 3a-3=3(7-a) | | 9*n-3=7(n+3)+2n | | -4(1+2m)-5m=61 | | 1/20-1/38=x | | y=7-3*-2 | | s-3=5-8 | | y=7-3*2 | | 3-6s+8s=9 | | 2x=1.5x+1 | | 3x+2=2+(2x-7) | | -4(2x+8)=8x | | X^2+x+7.5=0 | | -4+10[6x-7(8+3x)]= | | 420a=15 | | 4t+8j=10 |